Carrying messages of "Peace" to the world: Landscape, discourses, and practices of peace in Hiroshima - Yokoyama, Yuichi (AUC Knowledge Fountain, 2018)
This thesis is my exploration of what the landscape of peace, onto which past relevant actors' discourses and practices of peace and my interlocutors' present practices of peace are inscribed, represents and silences, and how my interlocutors, who relate their activities to the concept peace, make sense of the concept peace. In the literature in the field of anthropology of peace, peace has been what is defined by the anthropologists, not by their interlocutors. In other words, the anthropologists' definitions of peace have silenced their interlocutors' understandings of peace. This whole thesis was written as a critique of how these anthropologists of peace have silenced their interlocutors' own understandings of peace. I explored how discourses and practices that actors involved related to the concept peace in the past and my interlocutors' present practices are inscribed onto the landscape. Hiroshima city has been explicitly designed as a "peace (memorial) city". Reconstruction of ruined Hiroshima as a "peace (memorial) city" enabled the city government to obtain special subsidies, with which the city government constructed many facilities including the Peace Memorial Park, but at the same time, it oppressed and silenced despondent voices and uncomfortable feelings of many citizens, the majority of whom were A-bomb victims. In the Peace Memorial Park, there are many objects such as buildings, monuments, and A-bombed trees, which were erected or have been preserved by a variety of actors who thought these objects symbolize their hope for peace. Many of the objects in the park represent the master narrative of peace in Hiroshima which links the atomic bombing with the concept peace. In my fieldwork, as a guide, I took my guests to a dozen of the objects in the park in my guided tours. My guided tour, which centered on what the objects in the Peace Memorial Park represent, contributed to the hegemonic narrative of peace, which silences many voices. In a Foucauldian sense, I was formed as a subject of the hegemonic discourse of peace in Hiroshima. With this as a backdrop, I inquired how my interlocutors make sense of the concept peace especially in relation to their activities that they relate to the concept peace. Although they clearly relate their activities to the concept peace, their thoughts on peace are rarely made manifest. The foregrounded concept peace silences their understandings of peace, which differs from one another. Many of my interlocutors' understandings of peace are counterposed to their understandings of what happened in Hiroshima.